Internal dosimetry study of [82Rb]Cl using a long axial field-of-view PET/CT - Mercolli, Lorenzo; Bregenzer, Carola; Diemling, Markus; Mingels, Clemens; Rominger, Axel; Sari, Hasan; Seibel, Sigrid; Sohlberg, Antti; Viscione, Marco; Caobelli, Federico (European journal of nuclear medicine and molecular imaging, 2024)
Purpose Long axial field-of-view (LAFOV) positron emission tomography (PET) systems allow to image all major organs with one bed position, which is particularly useful for acquiring whole-body dynamic data using short-lived radioisotopes like 82 Rb. Methods We determined the absorbed dose in target organs of three subjects (29, 40, and 57 years old) using two different methods, i.e., MIRD and voxel dosimetry. The subjects were injected with 407.0 to 419.61 MBq of [ 82 Rb]Cl and were scanned dynamically for 7 min with a LAFOV PET/CT scanner. Results Using the MIRD formalism and voxel dosimetry, the absorbed dose ranged from 1.84 to 2.78 μGy/MBq (1.57 to 3.92 μGy/MBq for voxel dosimetry) for the heart wall, 2.76 to 5.73 μGy/MBq (3.22 to 5.37 μGy/MBq for voxel dosimetry) for the kidneys, and 0.94 to 1.88 μGy/MBq (0.98 to 1.92 μGy/MBq for voxel dosimetry) for the lungs. The total body effective dose lied between 0.50 and 0.76 μSv/MBq. Conclusion Our study suggests that the radiation dose associated with [ 82 Rb]Cl PET/CT can be assessed by means of dynamic LAFOV PET and that it is lower compared to literature values.